Structure Based Refinement of a Humanized Monoclonal Antibody That Targets Tumor Antigen Disialoganglioside GD2 - Ahmed, Mahiuddin; Hu, Jian; Cheung, Nai-Kong V. (Frontiers in Immunology, 2014)
Disialoganglioside GD2 is an important target on several pediatric and adult cancer types including neuroblastoma, retinoblastoma, melanoma, small cell lung cancer, brain tumors, sarcomas, and cancer stem cells. We have utilized structural and computational methods to refine the framework of humanized monoclonal antibody 3F8, the highest affinity anti-GD2 antibody in clinical development. Two constructs (V3 and V5) were designed to enhance stability and minimize potential immunogenicity. Construct V3 contained twelve point mutations and had higher thermal stability and comparable affinity and in vitro tumor cells killing as the parental hu3F8. Construct V5 had 9 point mutations to minimize potential immunogenicity, but resulted in weaker thermal stability, weaker antigen binding, and reduced tumor killing potency. When construct V3 was combined with the single point mutation HC:G54I, the resulting V3-Ile construct had enhanced stability, antigen binding, and a nearly 6-fold increase in tumor cell killing. The resulting product is a lead candidate for clinical development for the treatment of GD2-positive tumors.